Intelligent Integration Algorithm of National Traditional Sports Culture Resources Based on Big Data - Xian-Bin Ai (Journal of Mathematics)
There is an information island between traditional national sports culture resources and realize the efficient real-time interconnection of resources. Therefore, this study proposed an intelligent integration algorithm of traditional national sports culture resources using big data that halts the said information island. Firstly, the complete data set is obtained by determining the time attenuation period of the weighted sample, and the mining parameters are based on the real value to realize the in-depth mining of the resource wisdom of traditional ethnic sports culture. Then, the query set of big data is constructed based on the results of weakly associated data mining, and the query of weakly associated data is completed through data repair. Finally, XML technology is used to run the schema to build a resource integration model. The experimental results show that compared with the traditional integration algorithm, the proposed algorithm can better solve the problem of information island among traditional ethnic sports culture resources at all levels and effectively maintain the stability of the storage environment of traditional ethnic sports culture resources while realizing the real-time interconnection of resources.